Demonstration Gardens in the University of Florida Cooperative Extension Service - Eva C. Worden; Cathy J. D'Angelo (EDIS, 2002)
This document is ENH 865, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 12, 2002.